1991
DOI: 10.1002/j.1460-2075.1991.tb07789.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C activation potently down-regulates the expression of its major substrate, 80K, in Swiss 3T3 cells.

Abstract: The amino acid sequence of 80K, the major acidic protein kinase C (PKC) substrate of Swiss 3T3 fibroblasts, was deduced from a cDNA nucleotide sequence. Overall, 25% of the predicted amino acid sequence is supported by direct protein sequence data. Southern blot analysis suggests that the mouse genome contains a single copy of this gene. Two 80K mRNA species, a major band of 2.25 kb and a minor band of 3.9 kb, were detected by Northern blot analysis. Stimulation of PKC by biologically active phorbol esters, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
2

Year Published

1992
1992
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 74 publications
4
59
2
Order By: Relevance
“…We have shown that the 100 kDa 2-5A synthetase, the enzymatic products of which have the capacity to inhibit protein synthesis and the stability of specific mRNAs, is up-regulated by PMCd at a post~transcriptional level 1471. In another study, Brooks et al [48] reported that activation of PKC in Swiss/3T3 cells by phorbol esters reduced the expression of its major phosphorylation substrate, ~80, apparently also by a post-transcriptional mechanism affecting the stability of its mRNA. It is therefore possible that similar molecular m~hanisms might be active in regulating the expression of EGF, PDGF-ol and other receptor molecules.…”
Section: Role Of Pkc-o! In ~E~~fftion Of Pi3gf Receptorsmentioning
confidence: 96%
“…We have shown that the 100 kDa 2-5A synthetase, the enzymatic products of which have the capacity to inhibit protein synthesis and the stability of specific mRNAs, is up-regulated by PMCd at a post~transcriptional level 1471. In another study, Brooks et al [48] reported that activation of PKC in Swiss/3T3 cells by phorbol esters reduced the expression of its major phosphorylation substrate, ~80, apparently also by a post-transcriptional mechanism affecting the stability of its mRNA. It is therefore possible that similar molecular m~hanisms might be active in regulating the expression of EGF, PDGF-ol and other receptor molecules.…”
Section: Role Of Pkc-o! In ~E~~fftion Of Pi3gf Receptorsmentioning
confidence: 96%
“…Various cDNA sequences inserted into the EcoRI site of pMV7 were stably expressed and yielded high-level production of the corresponding protein [ll]. For the present study, the 80-kDa MARCKS cDNA p803.3 isolated from a Swiss 3T3 cDNA library [7] was digested with EcoRI and the l-kb insert ligated into the EcoRI site down-stream of the 5' LTR of the pMV7 plasmid after gel purification. The resulting construct was called pMV7-80K.…”
Section: Expression Vector and Transfectionmentioning
confidence: 99%
“…10 pg DNA was digested with the restriction enzymes EcoRI or XbaI, separated in a 1% agarose gel, then transferred onto a Hybond-N' membrane (Amersham). The filters were hybridised with a gel-purified 843-bp Ball-EcoRI fragment of the 80-kDa MARCKS-coding region of clone p809.1 isolated from a Swiss 3T3 cDNA library [7]. The specific activity of the random-primed probe was 5 X 10' c p d p g .…”
Section: Southern-blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation occurs on serine at similar sites (up to 2.8 moles of s2P/mole of protein) in vitro and in vivo [5,8,9]. The 87 kDa protein has been cloned and sequenced from the brain and nonneuronal tissue of many species [10][11][12][13]. The gene codes for proteins of approximately 330 amino acids that are 60-70% identical in sequence although the phospho- rylated region is completely conserved.…”
Section: Introductionmentioning
confidence: 99%